Contributions of hemispheric dynamics in visual word recognition: uncovering familiarity effects through lateralized priming - Kim, Sangyub; Nam, Kichun (Frontiers in Psychology, 2024)
Introduction This investigation aimed to explore interhemispheric interactions in visual word processing with a focus on proficiency development. Given the asymmetrical specialization in visual word processing across hemispheres, the study hypothesized that the primary hemisphere predominantly regulates interhemispheric interactions. The familiarity effect, serving as a measure of visual word processing proficiency, was examined to determine how proficiency influences these interactions. Methods A primed-lateralized lexical decision task with a stimulus onset asynchrony (SOA) of 100 ms was employed. The task involved presenting primes and targets in parafoveal visual fields (left visual field/right visual field) to assess behavioral responses. By manipulating prime and target visual field locations, the study aimed to evaluate both inter- and intrahemispheric interactions during visual word processing. Results The findings revealed a significant interhemispheric familiarity effect in response times when the left visual field (LVF)/right hemisphere (RH) served as the prime and the right visual field (RVF)/left hemisphere (LH) as the target. Additionally, a significant intrahemispheric familiarity effect was observed within the LVF/RH condition, suggesting a prominent role of the RH in visual-perceptual processing during the development of visual word recognition proficiency. Discussion These results provide compelling evidence for asymmetric specialization between the hemispheres in visual word processing. The significant inter- and intrahemispheric familiarity effects underscore the importance of RH visual-perceptual processing in proficiency development. These insights enhance our understanding of interhemispheric dynamics in the evolution of visual word recognition proficiency, highlighting the complex coordination between hemispheres in facilitating fluent visual word processing.